Congenital Rhabdomyosarcoma of Tongue in a Newborn - Gurung, U; Srivastav, A; Guragain, R; Bhusal, CL (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 15-16 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6797